فقہ مقارن کا آغاز و ارتقاء اور اس کی عصر ی معنویت:عہد نبوی ﷺ سے عصر حاضر کے تناظر میں ایک تحقیقی مطالعہ : The Origin and Development of Comparative Jurisprudence and Its Spiritual Significance: A Research Study from the Prophetic Era to the Present Age - Ghulam Ullah; Muhammad Taha Ibrahim Dehlvi (International Research Journal of Arabic and Islamic Studies, 2024)
Islamic jurisprudence transcends mere legalities; it encompasses a comprehensive ethical framework guiding both individual conduct and societal affairs. From the era of the Prophet Muhammad ﷺ who ignited a profound thirst for knowledge among his Companions, to the present age of globalization and technological advancement, the evolution of Islamic jurisprudence has been marked by adaptation and response to contemporary challenges. Post-Companions, jurists and mujtahids employed ijtihad to address new issues using Quranic principles and Prophetic traditions. In today's globalized world, economic complexities have necessitated innovative solutions rooted in Sharia. This has spurred a collective approach to ijtihad, incorporating insights from all four schools of jurisprudence, thus ensuring relevance and applicability across diverse contexts. Pakistan, influenced by this collective jurisprudential approach, emphasizes the study of fiqh al-maqaran in its religious schools, fostering a nuanced understanding of comparative jurisprudence. This approach promotes flexibility and inclusivity in fatwa issuance, accommodating varying societal needs while upholding Sharia principles. This Research explores the significance of collective ijtihad in addressing contemporary socio-economic, political, cultural, and legal challenges within Muslim societies, underscoring its role in the evolution and relevance of Islamic jurisprudence in the modern era.